Introduction to the theoretical and intellectual foundations of the cognitive acceleration strategy (constructivist cognitive theory as a model) (Al-Academy, 2025)
Today's world is characterized by a knowledge explosion, witnessing a revolution in knowledge, information, and technology that encompasses all aspects of human life. The focus is no longer on the quantity of information acquired, but rather on how to acquire and properly utilize it, enabling individuals to absorb these scientific changes and significant achievements in various fields. This revolution has presented the educational system and those in charge of it with difficult challenges, including preparing members of society to absorb the rapid scientific developments by developing their abilities to research, analyse, ask questions, evaluate information, and invest their minds in a way that achieves maximum benefit for the sake of building and developing society. Based on this, the importance of the emergence of modern teaching methods that are compatible with the knowledge explosion and technological progress present in the world has emerged. There has become an urgent need to use teaching models and methods that emphasize the role of the learner and make him the centre of activity in the educational process. This is what the modern trend in education calls for, which emphasizes the necessity of involving the student in the learning process and his active contribution to the lesson through the activities he undertakes himself. This paves the way for the transition from teaching to learning, instills positive attitudes towards learning, and helps him understand the academic material that includes facts, information, and laws, especially by discouraging students from being inclined toward experimentation. The student's goal has become clear: passing the subject, not learning and knowledge. According to the above, the teaching method and its strategies must be part of this development and change and must go beyond all that is traditional in education to what is better. Perhaps one of the effective methods today is that which makes the learner the focus of the educational process, which helps in the rapid learning of knowledge, the excitement of their thinking and solving problems in a scientific way, and enhances their ability to develop and innovate, which imposes the cognitive foundation of such strategies in order to stand on their circumstances and the mechanisms for their procedural employment.